Sosialisasi BPBL dan Peningkatan Aksesbilitas Listrik: (Studi di Desa Fadoro Sitolu Hili Lahewa) - Maria Magdalena Bate’e; Dian Purnama Sari Ndruru; Putri Yanti Telaumbanua; Kristianus Hia; Viktorianus Zamasi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effectiveness of the socialization of the New Electricity Installation Assistance Program (BPBL) in increasing public understanding and encouraging electricity access for poor households in Fadoro Sitolu Hili Village, Lahewa District. The BPBL program is a government policy that provides free electricity installation assistance for underprivileged communities who have not yet enjoyed independent electricity connections. This study used a descriptive-qualitative approach with observation, documentation, and brief interviews with village officials and target residents. The results of the discussion indicate that the BPBL socialization was able to increase public knowledge regarding the program's objectives, recipient criteria, benefits, required documents, and registration procedures. In addition, the socialization conducted directly in the village strengthened community trust in the government program and clarified that the BPBL is free of charge. Thus, the BPBL socialization plays a significant role in accelerating equitable access to electricity and supporting improvements in the quality of life of rural communities.